Strategi Coping pada Perempuan Korban Pelecehan Seksual di Perguruan Tinggi Sulawesi Selatan - ERINA SYUKUR; Nur Afiah; Emilia Mustary; Adnan Achiruddin Saleh; Astinah (Institut Agama Islam Negeri Curup, 2026)
This study aims to identify and explain the forms of coping strategies used by female students who were victims of sexual harassment at a university in South Sulawesi, analyze the process of their implementation, and assess their impact on the victims' mental health. This study used a qualitative approach with a case study design on four female students who were victims of sexual harassment. Data were obtained through in-depth interviews and analyzed thematically using ATLAS.ti based on the Transactional Stress Model and religious coping theory. The results revealed three main forms of coping strategies: emotion-focused coping, problem-focused coping, and religious coping. These findings indicate that coping strategies are dynamic according to the emotional state, social support, and spiritual experience of the victim. Emotion-focused coping is dominant in the early phase of trauma, while problem-focused coping and religious coping develop with increasing social support and the process of self-meaning. This study provides a conceptual contribution to the integration of psychological and religious coping in the context of a religious campus, and offers practical implications for the development of trauma-informed care-based mentoring that is sensitive to the psychological and spiritual dimensions of victims.